Effect of chemical pressure on the local structure of La1−xSmxFeAsO system. (13th January 2015) - Iadecola, A; Joseph, B; Paris, E; Provino, A; Martinelli, A; Manfrinetti, P; Putti, M; Saini, N L
Abstract: We have studied the effect of chemical pressure on the local structure of La Sm x FeAsO oxypnictides. The combination of arsenic K-edge and rare-earth (RE = La, Sm) L3 -edge x-ray absorption spectra has permitted us to determine local bondlengths and unoccupied electronic states with varying chemical pressure controlled by the size difference of La and Sm. The Fe–As distance is hardly affected by the chemical pressure, and remains covalent as shown by As K-edge extended x-ray absorption fine structure (EXAFS) analysis. On the other hand, the As–RE and As–As distances show a gradual change. The changes indicate a larger effect of chemical pressure in the REO spacer layer and on the interlayer interactions, consistent with x-ray absorption near edge structure (XANES) data. The results suggest that interlayer atomic correlations are likely to have an important role in the physical properties of the La Sm x FeAsO parent phases of the superconducting oxypnictides.